1965
DOI: 10.1139/v65-210
|View full text |Cite
|
Sign up to set email alerts
|

CONFORMATIONAL STUDIES ON SYNTHETIC POLY-α-AMINO ACIDS: THE HELICAL SENSE OF POLY-L-TRYPTOPHAN: OPTICAL ROTATORY DISPERSION STUDIES

Abstract: The synthesis of high n~olecular weight (100 000 to 200 000) polymers and copolymers of L-tryptophan and y-benzyl-L-glutamate is reported. The optical rotatory dispersion (0.r.d.) of these polypeptides is recorded in the wavelength range 540-320 mp and the bo values of the Moffitt equation, using X O = 212 mp, are listed. Poly-L-tryptophan has a bo value of f 570 in dimethylforman~ide (DMF). A linear relationship exists between this value, bo values of copolymers of various ratios of L-tryptophan and y-benzyl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Until 229 nm, the FSP-M shows linear response, and then it becomes negative, with a peak between 254 and 231 nm, and a minimum negative at ≈ 241 nm. Fasman et al described a peak at 276 nm in the CD spectrum of L-Tryptophan, explaining that it represents a superposition of the ␣-helix bands and of the strong aromatic chromophore bands which are present in the near UV region [40]. This argument is in agreement with the applied Reed's reference, which describes a 100% ␣-helix structure.…”
Section: Secondary Structure Of Fsp-e and Fsp-mmentioning
confidence: 62%
“…Until 229 nm, the FSP-M shows linear response, and then it becomes negative, with a peak between 254 and 231 nm, and a minimum negative at ≈ 241 nm. Fasman et al described a peak at 276 nm in the CD spectrum of L-Tryptophan, explaining that it represents a superposition of the ␣-helix bands and of the strong aromatic chromophore bands which are present in the near UV region [40]. This argument is in agreement with the applied Reed's reference, which describes a 100% ␣-helix structure.…”
Section: Secondary Structure Of Fsp-e and Fsp-mmentioning
confidence: 62%
“…The b 0 value in DMF calculated by Moffitt's equation was +495. Fasman et al performed the conformation analysis of poly(Trp) with a molecular weight 123 000 g mol −1 , and reported that the poly(Trp) forms a α‐helix structure with b 0 value of +570 30–32. Although the poly(Trp) used in this study can form α‐helix structures, the ordered structure seems to have not been formed at its molecular terminal since the degree of polymerization was not sufficiently high.…”
Section: Resultsmentioning
confidence: 85%
“…The b 0 value in DMF calculated by Moffitt's equation was C495. Fasman et al performed the conformation analysis of poly (Trp) with a molecular weight 123,000 g/mol, and reported that the poly(Trp) forms a a-helix structure with b 0 value of C570 [29][30][31]. Although the poly(Trp) used in this study can form a-helix structure, the ordered structure seems to have not been formed at its molecular terminal since the degree of polymerisation is not sufficiently high.…”
Section: Secondary Structure Of Pheg-block-poly(trp)mentioning
confidence: 79%